Prihatin Expedition Programme by UMP Foundation Engages the Pekan Community - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
PEKAN, 18 June 2023 - The ‘Prihatin’ Expedition@Masjid at-Taqwa programme organized by the University Malaysia Pahang (UMP) Foundation marks the beginning of several ‘Prihatin’ (concerned) Expedition UMP 21 programmes that will be conducted in selected locations, including Pahang, Johor, Sabah, Thailand, and Indonesia, to gain experience and provide assistance to the communities.